A cross-sectional study of cutaneous changes during pregnancy in a tertiary care hospital in Northern India - Chaudhary, Azra Ferheen; Goel, Shitij; Mehta, Archana (International Journal of Research in Dermatology, 2022)
Background: Women undergo profound changes during pregnancy, making them susceptible to a number of dermatological manifestations. We aimed to determine the frequency and pattern of skin changes during pregnancy. Methods: A cross-sectional observational study was conducted among 400 pregnant women presenting to the Outpatient department of a Tertiary Care Centre in Northern India. Results: A total of 400 pregnant mothers fulfilling inclusion criteria were included. The pigmentary changes were the most common physiological change seen in 90.8% (n=363) of pregnant women. The most common pigmentary change was secondary areola seen in 83% (n=332) women, followed by linea nigra seen in 37.5% (n=150) pregnant women. Vascular changes were seen in 13% (n=52), non- pitting pedal edema being the most common 10.25% (n=41). Connective tissue changes were seen in 62.25% (n=249) of pregnant women, striae gravidarum being the most common (n=242). The most common specific dermatoses of pregnancy was atopic eruption of pregnancy seen in 4.25% (n=17), followed by intrahepatic cholestasis of pregnancy (n= 14). 3 cases (0.75%) of Polymorphic eruption of pregnancy were seen. 1 case of Pemphigoid gestationis was seen in the third trimester. Approximately 17% of pregnant women were positive for infections among which fungal infection was the most common infection affecting pregnant women, seen in 11.2% (n=45) participants. Conclusions: The dermatoses of pregnancy are common and have a range of dermatological manifestations apart from their specific pattern; in order to manage and treat them appropriately, proper attention needs to be given.